2018
DOI: 10.1242/dev.169870
|View full text |Cite
|
Sign up to set email alerts
|

Molecular bases for the constitutive photomorphogenic phenotypes in Arabidopsis

Abstract: The transition from skotomorphogenesis to photomorphogenesis is regulated in part by the COP1/SPA complex and phytochromeinteracting factors (PIFs) in Arabidopsis. The constitutive photomorphogenic (cop) phenotypes of cop1 and spaQ mutants have been shown to result from a high abundance of positively acting transcription factors. Here, we show that the four major PIF proteins are unstable in cop1 mutants and that overexpression of PIF1, PIF3, PIF4 and PIF5 suppresses cop1 phenotypes in the dark. A comparison o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…Parallel to and partially dependent on COP1/SPA, the PIFs also repress light signalling. Light‐activated phytochromes bind PIFs and repress their activity by promoting their phosphorylation and targeting for degradation as well as by inhibiting their association with target promoters (Bauer et al ., 2004; Shen et al ., 2005; Al‐Sady et al ., 2006; Shen et al ., 2008; Park et al ., 2012; Lee and Choi, 2017; Pham et al ., 2018; Paik and Huq, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to and partially dependent on COP1/SPA, the PIFs also repress light signalling. Light‐activated phytochromes bind PIFs and repress their activity by promoting their phosphorylation and targeting for degradation as well as by inhibiting their association with target promoters (Bauer et al ., 2004; Shen et al ., 2005; Al‐Sady et al ., 2006; Shen et al ., 2008; Park et al ., 2012; Lee and Choi, 2017; Pham et al ., 2018; Paik and Huq, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, COP1 is regarded as a central negative factor on plant photomorphogenesis [22,23]. It has been reported that COP1-SPAs complex not only target positive regulators (HY5, HFR1, etc) for ubiquitination and degradation, but also promote the accumulation of negative factors such as PIFs [17,24,25]. We found four COP1 transcripts, among which only one transcript had relative high expression.…”
Section: Key Regulators In Light Signaling Pathwaymentioning
confidence: 71%
“…Although the effects of light quality on photomorphogenesis and the underlying molecular mechanism has been well studied in Arabidopsis [16][17][18], it is poorly understood in other plant species. We tested the effects of light quality on the hypocotyl elongation in eight eudicot species.…”
Section: Resultsmentioning
confidence: 99%
“…; Pham et al . ), and sunflower is a model organism used to study global warming (Badoin et al . ), the pioneering S. alba work of Mohr and collaborators laid the foundations for these more recent developments in plant sciences.…”
Section: Discussionmentioning
confidence: 99%